The problems of development of the Czech historic novel in the 1970–80s - Vostrykova, Alena U. (Journal of the Belarusian State University. Philology, 2019)
The author of the article comes to the conclusion that in the 1970–80s the Czech historical novel represents such new phenomena as emphasized attention to modernity (V. Neff), the use of artistic possibilities of documentary sources in the work (M. V. Kratokhvil). Documentality and publicism allow us to appeal to the modern reader, to correlate the past and the present. We also need to highlight the tendency to demythologize history (V. Erben, O. Danek). At the same time, the traditional type of historical novel, represented by the V. Kaplitsky, B. Rzhiga, F. Kubki and others, remains productive. The thematic palette of novels of the 1970–80s is very wide. The authors turn to the ancient epochs, comprehend the connection of generations, the problems of the succession of human existence and continuity. The role and place of the parody in the historical novel, which is clearly seen in the trilogy of V. Neff «Queens have no legs», «The ring of the Borgias», «The beautiful sorceress» can be examined as a special problem. It is also possible to highlight the entertaining tendency in historical literature, the desire for adventure and pseudo-historical stories, somewhere even a desire for rapprochement with mass literature, which, surprisingly, did not cause resistance from authorities of the period of normalization. Many historical novels become philosophical parables, where history appears as one of the heroes. It expresses the cruelty of the surrounding world, full of tragedy and accidents.